Evaluasi Status Pemanfaatan Cumi-Cumi Sebagai Bahan Pertimbangan Keberlanjutan Usaha Rumahtangga Pengolah Cumi Asap Teluk Prigi Kabupaten Trenggalek - Purwanti, Pudji; Intyas, Candra Adi; Sofiati, Dwi; Fattah, Mochammad; Anandya, Asyifa (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Squid is one of the leading export commodities whose potential availability is monitored by the government. This research aims to evaluate the status of squid utilization as a consideration for the sustainability of squid-based smoke processing businesses in Prigi Regency. The analysis used in this research is Gordon-Scheafer bioeconomics. The fishing gear used to catch squid includes 1-boat ring seine, 2-boat ring seine, gill net, paying, trolling line and hand line. The average production of squid commodities from 2014-2022 is 26,396 kg, with a standard effort of 340 yearly trips. Prigi PPN squid fishing activities are economic and biological overfishing because the real average fishing effort exceeds the sum of MEY and MSY efforts. The level of squid utilization tends to approach over-exploited and exceeds 17.5% of the allowable catch. This condition can affect the fulfilment of production needs for processed squid smoke.